Bioprosthetic vs. Mechanical Mitral Valve Replacement for Rheumatic Heart Disease in Patients Aged 50–70 Years - Yu, Jun; Wang, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Rheumatic heart disease (RHD) is a critical problem in developing countries and is the cause of most of the cardiovascular adverse events in young people. In patients aged 50 to 70 years with RHD requiring mitral valve replacement (MVR), deciding between bioprosthetic and mechanical prosthetic valves remains controversial because few studies have defined the long-term outcomes. Methods: 1691 Patients aged 50 to 70 years with RHD who received mechanical mitral valve replacement (MVRm) or bioprosthetic mitral valve replacement (MVRb) were retrospectively reviewed in Fuwai hospital from 2010 to 2014. Follow-up ended December 31, 2021; median duration was 8.0 years (IQR,7.7-8.3 years). Propensity score matching at a 1:1 ratio for 24 baseline features between MVRm and MVRb yielded 300 patient pairs. The primary late outcome was postoperative mid- to long-term all-cause mortality. Results: Ten-year survival after MVR was 63.4% in the MVRm group and 63.7% in the MVRb group (HR,0.91;95%CI,0.69-1.21; P=0.528). The cumulative incidence of mitral valve reoperation was 0.0% in the MVRm group and 1.2% in the MVRb group (HR,0.92;95%CI,0.69-1.21; P=0.530). The cumulative incidence of stroke was 5.5% in the MVRm group and 6.1% in the MVRb group (HR,0.89;95%CI,0.67-1.18; P=0.430). The cumulative incidence of major bleeding events was 3.3% in the MVRm group and 3.4% in the MVRb group (HR,0.92;95%CI,0.70-1.22; P=0.560). Conclusions: In patients aged 50 to 70 years with RHD who underwent mitral valve replacement, there was no significant difference on survival, stroke, mitral valve reoperation and major bleeding events at 10 years. These findings suggest mechanical mitral valve replacement may be a more reasonable alternative in patients aged 50 to 70 years with rheumatic heart disease.